Collaborative Modelling of Activities to Support the Teaching of Programming: An Empirical Study - Oscar Revelo-Sánchez; César A. Collazos; Alexander A. Barón (Interaction Design and Architecture(s))
Although the practical benefits of incorporating collaborative work into education have been highlighted, there has been little emphasis on a fundamental part: the design of the inherent collaborative processes. Collaborative engineering emphasises the use of collaboration patterns and thinkLets as primary design units, with reusability as an essential goal. This paper presents the design and validation of the collaborative activity “Peer Code Review”, aimed at supporting the teaching of introductory programming courses using collaboration patterns and thinkLets. A controlled experiment with 79 students of introductory programming courses demonstrated the effectiveness of the proposed approach. The results showed that students in the experimental groups achieved significantly higher grades than those in the control groups. These results validate the positive impact of the peer code review activity on academic performance and confirm its potential as an effective collaborative learning strategy for teaching programming.